Perbandingan dinasti umayyah dan abbasiyah dalam membangun peradaban islam: Studi historis atas karakteristik pemerintahan dan kontribusi peradaban dua dinasti islam klasik - Balya Barlaman, Ahmad Firjaun (Maliki Interdisciplinary Journal, 2025)
This article examines two major dynasties in Islamic history— the Umayyad and Abbasid Caliphates— focusing on their governing characteristics and contributions to Islamic civilization. The Umayyad Caliphate (661–750 CE), centered in Damascus, is known for establishing hereditary monarchy, implementing Arabization policies, and leading vast military expansions across Europe and Asia. In contrast, the Abbasid Caliphate (750–1258 CE), based in Baghdad, promoted a more inclusive and cosmopolitan administration, emphasizing support for knowledge, science, arts, and cultural development. Using a comparative approach, the article highlights the differing foundations of both dynasties: the Umayyads prioritized military strength and centralized authority, while the Abbasids advanced intellectual and cultural progress through decentralization and openness to non-Arabs. Both dynasties played significant roles in shaping classical Islamic civilization politically, economically, and intellectually. The legacy of their achievements and eventual decline serves as a valuable lesson for contemporary Muslim societies on the importance of justice, knowledge, and inclusivity in building a flourishing civilization.